THE PREMIUM OF TRANSPARENCY: ASSESSING THE NON-LINEAR IMPACT OF ESG RATING DISCREPANCIES ON CORPORATE COST OF DEBT DURING MACROECONOMIC UNCERTAINTY - Wulandari Sungkowo Tri Putri; Syafiq Amir; Haziq Idris (Journal Markcount Finance, 2026)
Environmental, Social, and Governance (ESG) ratings have become increasingly influential in shaping corporate financing decisions and stakeholder assessments within global capital markets. Growing reliance on ESG information has enhanced the importance of transparency and sustainability disclosures; however, substantial discrepancies among ESG rating providers continue to raise concerns regarding information reliability, comparability, and credibility. Such inconsistencies may create uncertainty for creditors, particularly during periods of macroeconomic instability when risk assessment becomes more challenging. This study aims to examine the non-linear impact of ESG rating discrepancies on corporate cost of debt and to evaluate the moderating role of macroeconomic uncertainty in shaping this relationship. A quantitative research design employing panel data analysis was utilized. The study analyzed publicly listed non-financial firms observed between 2014 and 2023, using ESG ratings obtained from multiple providers alongside financial and macroeconomic indicators. Non-linear regression models and interaction analyses were applied to assess the effects of ESG rating divergence on borrowing costs. Findings indicate that ESG rating discrepancies are positively associated with corporate cost of debt and that this relationship follows a non-linear pattern. Borrowing costs increase modestly at lower levels of divergence but rise substantially once discrepancies exceed critical thresholds. Macroeconomic uncertainty significantly amplifies these effects, increasing creditor sensitivity to sustainability-related information ambiguity. The study concludes that transparency represents a valuable financial asset, as firms demonstrating greater ESG rating consistency benefit from lower financing costs and stronger creditor confidence during uncertain economic conditions.